Adaptive mechanisms in quinoa for coping in stressful environments: an update - Ain, Qura Tul; Siddique, Kiran; Bawazeer, Sami; Ali, Iftikhar; Mazhar, Maham; Rasool, Rabia; Mubeen, Bismillah; Ullah, Farman; Unar, Ahsanullah; Jafar, Tassadaq Hussain (PeerJ, 2023)
Quinoa (Chenopodium quinoa) is a grain-like, genetically diverse, highly complex, nutritious, and stress-tolerant food that has been used in Andean Indigenous cultures for thousands of years. Over the past several decades, numerous nutraceutical and food companies are using quinoa because of its perceived health benefits. Seeds of quinoa have a superb balance of proteins, lipids, carbohydrates, saponins, vitamins, phenolics, minerals, phytoecdysteroids, glycine betaine, and betalains. Quinoa due to its high nutritional protein contents, minerals, secondary metabolites and lack of gluten, is used as the main food source worldwide. In upcoming years, the frequency of extreme events and climatic variations is projected to increase which will have an impact on reliable and safe production of food. Quinoa due to its high nutritional quality and adaptability has been suggested as a good candidate to offer increased food security in a world with increased climatic variations. Quinoa possesses an exceptional ability to grow and adapt in varied and contrasting environments, including drought, saline soil, cold, heat UV-B radiation, and heavy metals. Adaptations in salinity and drought are the most commonly studied stresses in quinoa and their genetic diversity associated with two stresses has been extensively elucidated. Because of the traditional wide-ranging cultivation area of quinoa, different quinoa cultivars are available that are specifically adapted for specific stress and with broad genetic variability. This review will give a brief overview of the various physiological, morphological and metabolic adaptations in response to several abiotic stresses.
Keywords: Quinoa; Betalains; Andean indigenous culture; UV-B radiations; Salinity; Genetic variability